PESANTREN: GENEALOGI, DINAMIKA, DAN NASIONALISME - Aziz, Jamil Abdul (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2018)
This paper adresses  three things related to  pesantren (Islamic traditional education system) in Indonesia. First, elements genealogy: the origin of the emergence of multicultural pesantren in Indonesia. Second, the dynamic elements of pesantren education from time to time, how schools are able to maintain growth and existence amidst currents of modern education is increasingly passionate. Third, what are the key elements of pesantren, especially developed nationalizm by kyai Nahdliyin, so as to print the generation that participated guarding the integrity of the Unitary Republic of Indonesia (NKRI).